Chapter Massimo Quaini, la passione per la cartografia storica con uno sguardo rivolto al futuro - Poli, Daniela (Territori, 2021)
The essay traces back the scientific dialogue between the author and Massimo Quaini about the contemporary usefulness of the geographer-cartographer figure, perfected during the period of the great absolute monarchies. In this path, which ranges among memories, literature, poetry, the story of the elaboration of the Charter celebrating the historical-morphological identity of the Levanto territory drawn up during the elaboration of the Levanto PUC finds space. In the text, Quaini's fundamental contribution emerges in highlighting the historical cartographer as a mediator of knowledge, an aspect that is necessary today to recover in order to create an urban planning account capable of putting at the centre of the project the place, in its various expressive forms, and the settled community.